Clinicopathological Study of 30 Cases of Peripheral T-cell Lymphoma with Hodgkin and Reed-Sternberg-like B-cells from Japan. (April 2017) - Eladl, Ahmed E.; Satou, Akira; Elsayed, Ahmed Ali; Suzuki, Yuka; Kato, Seiichi; Asano, Naoko; Nakamura, Shigeo
Abstract : The presence of Hodgkin and Reed-Sternberg (HRS)-like B-cells in peripheral T-cell lymphoma (PTCL) is rare and its clinicopathological features still remain unclear. Here, we describe 30 cases of PTCL with HRS-like B-cells from Japan. Twenty-three cases (77%) presented evidence of follicular T-helper phenotype (TFH ) derivation: 12 were angioimmunoblastic T-cell lymphoma and 11 PTCL with TFH phenotype (PTCL-TFH). The remaining seven cases were diagnosed as PTCL, not otherwise specified (PTCL-NOS). Epstein-Barr virus (EBV) reactivation was detected in 25 cases (83%), but HRS-like B-cells were EBER + in only 20 cases (67%). The median age at diagnosis was 77 years (range, 39-91 y), including 24 patients (80%) were older than 60 years of age. Most of the patients presented at an advanced clinical stage and were associated with higher risk according to the International Prognostic Index. The 3-year overall and progression-free survival rates were 44% and 27%, respectively. No significant clinicopathological differences were detected between PTCL-TFH, PTCL-NOS and the angioimmunoblastic cases. Cases with EBER + HRS-like B-cells were associated with inferior overall and progression-free survival compared to those with EBER − HRS-like B-cells, but the difference was not significant. In conclusion, HRS-like B-cells were found in a subset of T-cell lymphomas, especially in association with the TFH phenotype and EBV reactivation. These cells have a tendency to affect elderly patients and to be associated with advanced clinical stages and dismal prognosis. The EBV status of HRS-like B-cells does not seem to affect the clinicopathological features of this group of PTCLs.